People's Republic of China-Hong Kong Special Administrative Region : Selected Issues. (IMF Staff Country Reports; Country Report, 2002)
This Selected Issues paper examines the economic integration between Hong Kong Special Administrative Region (SAR) and the Mainland of China. Hong Kong SAR's economic links with the Mainland expanded rapidly in the 1980s and in the first part of the 1990s, with Hong Kong SAR becoming the most important trade and international fundraising center for the Mainland. Since Hong Kong SAR's return to China's sovereignty, integration between the two economies has deepened, notwithstanding the Asian crisis.